Competition on paper: artifacts of visualization in antitrust policy - Gustavo Onto (economic sociology_the european electronic newsletter, 2019)
In April 2013, while I was undertaking fieldwork at the Brazilian antitrust authority - the Administrative Council for Economic Defense (CADE) - I had lunch with one of the advisors who was responsible for analyzing corporate requests for authorization of mergers and acquisitions. The reports she prepared were used as the basis for the final ruling by a member of the panel of the six CADE commissioners who decide whether or not the merger can go ahead. Just before entering the restaurant, the advisor excused herself for a few minutes to go and photograph shelves in a nearby pharmacy. The photographs were for a report she was drafting for a case involving the potential merger of two major producers of condoms. The report was favorable to the merger. She told me that she was also asking friends and family located in various states in Brazil to take similar photos of pharmacy stands, which she then intended to use in support of her line of argument...
Keywords: 330